Cell-assembled extracellular matrix (CAM) sheet production: Translation from using human to large animal cells. (February 2021) - Torres, Yoann; Gluais, Maude; Da Silva, Nicolas; Rey, Sylvie; Grémare, Agathe; Magnan, Laure; Kawecki, Fabien; L'Heureux, Nicolas
We have created entirely biological tissue-engineered vascular grafts (TEVGs) using sheets of cell-assembled extracellular matrix (CAM) produced by human fibroblasts in vitro . A large animal TEVG would allow long-term pre-clinical studies in a clinically relevant setting (graft size and allogeneic setting). Therefore, canine, porcine, ovine, and human skin fibroblasts were compared for their ability to form CAM sheets. Serum sourcing greatly influenced CAM production in a species-dependent manner. Ovine cells produced the most homogenous and strongest animal CAM sheets but remained ≈3-fold weaker than human sheets despite variations of serum, ascorbate, insulin, or growth factor supplementations. Key differences in cell growth dynamics, tissue development, and tissue architecture and composition were observed between human and ovine. This study demonstrates critical species-to-species differences in fibroblast behavior and how they pose a challenge when attempting to substitute animal cells for human cells during the development of tissue-engineered constructs that require long-term cultures.